Organizational Climate in Sports Institutions and its Relationship to Administrative Level Cooperation Among Administrative Staff - Mahdi Sayed Attia (Jurnal Pendidikan Kepelatihan Olahraga: PEJUANG, 2026)
This study aims to identify organizational climate level and administrative cooperation level among administrative staff working in sports institutions in Maysan Governorate, as well as to reveal nature of correlation between both concept.  researcher adopted a descriptive approach with a correlational method, as it was suitable for study outcome and problem. Community consisted of administrative staff working in sports institutions, while sample comprised 120 individuals selected randomly. To collect data,  researcher used two scales: Organizational Climate Scale developed by Al-Bakri and Hazem (2016), and Administrative Cooperation Scale developed based on relevant administrative literature. Both scales were based on a five-point Likert scale. Results showed that administrative staff have a good level of organizational climate and a high level of administrative cooperation, they also showed a strong, statistically significant positive correlation between organizational climate and administrative cooperation. Concluded that improving organizational climate directly contributes to enhancing administrative cooperation among staff, which positively impacts institutional performance. Recommended that focusing on developing work environment within sports organizations, promoting effective leadership styles, and fostering a spirit of teamwork among employees.